(3GdJHQ GdeSHhc aj Pjd GdSdhcs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s ((3eMeO Hf CMeO Hf eMeO Hf CMeO GdTcHj GdMfaj s)
(3ChdgG (B:s
(3hHYO aYde GdMOjK af ef afhf GdMOjK GdfHhi s
(3BNQgG (B:s
(3eef YdeJg dbH HGdefUhQ CjVkG ef GdNdaGA hGdedhc CHh HcQ Hf eMeO Hf bdGhhf s
(3GfXQ Qbe (B136 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjd s
Keywords: (3GdJGQjNs